Lagenorhynchus albirostris J. E. Gray 1846 - Galatius, Anders; Kinze, Carl Christian (Zenodo, 2016)
Lagenorhynchus albirostris J. E. Gray, 1846a White-beaked Dolphin Delphinus Tursio Brightwell, 1846:21, plate 1. Not Delphinus tursio Fabricius, 1780. Lagenorhynchus albirostris : J. E. Gray. 1846a:84. No type locality specified, but stated as “North Sea, coast of Norfolk ” by Gray (1846b:35); restricted by Gray (1850) to Great Yarmouth. First use of current name combination. Delphinus albirostris : J. E. Gray, 1846b:35, plate 10. Incorrect reference to Lagenorhynchus albirostris (Gray, 1846a) Delphinus pseudotursio Reichenbach, 1846:plate 24, figure 76. New name based on Brightwell’s (1846) description (see “Nomenclatural Notes”). Delphinus Ibsenii Eschricht, 1846:297. Type locality: “Agger Tange,” West coast of Jutland, Denmark. Delphinus (Lagenorhynchus) albirostris: van Beneden, 1860:28. Name combination. CONTEXT AND CONTENT. Order Cetacea, suborder Odontoceti, family Delphinidae. Subfamily assignment remains unsettled. Traditionally, the genus Lagenorhynchus comprised 6 shortsnouted delphinid species. Molecular research, however, has found this grouping to be polyphyletic, that is, comprising at least 2 unrelated lineages: (1) the Pacific and Southern ocean members ( L. obliquidens , and L. obscurus , L. australis , and L. cruciger , respectively), assigned to the subfamily Lissodelphininae; and (2) the 2 North Atlantic members of the genus ( L. albirostris and L./ Leucopleurus acutus — Cipriano 1997; LeDuc et al. 1999; Harlin-Cognato and Honeycutt 2006; McGowen et al. 2009; McGowen 2011; Banguera-Hinestroza et al. 2014). Molecular studies addressing the relationship between the latter 2 species have provided conflicting results (LeDuc et al. 1999; Harlin-Cognato and Honeycutt 2006; Banguera-Hinestroza et al. 2014). All studies agree that the taxa have basal positions in the Delphinidae phylogeny, but they either represent separate lineages (subfamilies) within the dolphin family (Delphinidae) or they are indeed sister species and form their own subfamily Lagenorhynchinae (Banguera- Hinestroza et al. 2014). ...